NILAI-NILAI AQIDAH DALAM NOVEL AYAT-AYAT CINTA 2 KARYA HABIBURRAHMAN EL SHIRAZY - Mery Misri Atin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This article is the result of research on the novel of Ayat-Ayat Cinta 2 by Habiburrahman El Shirazy which aims to describe the values of aqeedah in the novel. This research is library research using a qualitative approach that is interpreted descriptive analysis. The data collection method used by the writer is the documentation method. Then the data analyzed by the researcher uses content analysis techniques. The results showed that the aqeedah aspect found the values of aqeedah in the pillars of faith such as believing in Allah, believing in the angels of Allah, believing in the books of Allah, believing in the messengers of Allah, believing in the last day, and believing in destiny (qadha and qadar). Keywords: Nilai-nilai, aqidah, dan novel Ayat-Ayat Cinta 2.